Evaluation of the options by the consumers in process of buying enterprises`s goods - Belova, Tatyana; Mosiyevych, V.; Krainiuchenko (Fornolyak), Olga (My University, 2013)
It was made the analysis of one of the most important stage of the process of consumer decision to buy goods. This stage is estimation and choice among several alternative products or brands the one which would satisfy the buyer. It was explained the essence of two methods of assessment consumers’ preferences: the cost method of consumer’s characteristics and model of the expected value.
Keywords: consumer value; споживча вартість; купівля товару; кафедра маркетингу